Criminal Code of the Republic of Kazakhstan : through the prism of time (1997-2003) - Sartayeva Наталья Абаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The proposed article is one of a series of articles aimed at the study of the improvement of the existing Criminal Code of Republic of Kazakhstan from its adoption date till nowadays. This article is devoted to the years 1997-2003.